Cervical Spine Fractures: Who Really Needs CT Angiography?. Issue 23 (1st December 2019) - Fourman, Mitchell S.; Shaw, Jeremy D.; Vaudreuil, Nicholas J.; Dombrowski, Malcolm E.; Wawrose, Rick A.; Boakye, Lorraine A.T.; Alarcon, Louis H.; Lee, Joon Y.; Donaldson, William F.
Abstract : Study Design: Retrospective cohort study. Objective: Compare a novel two-step algorithm for indicating a computed tomography angiography (CTA) in the setting of a cervical spine fracture with established gold standard criteria. Summary of Background Data: As CTA permits the rapid detection of blunt cerebrovascular injuries (BCVI), screening criteria for its use have broadened. However, more recent work warns of the potential for the overdiagnosis of BCVI, which must be considered with the adoption of broad criteria. Methods: A novel two-step metric for indicating CTA screening was compared with the American College of Surgeons guidelines and the expanded Denver Criteria using patients who presented with cervical spine fractures to a tertiary-level 1 trauma center from January 1, 2012 to January 1, 2016. The ability for each metric to identify BCVI and posterior circulation strokes that occurred during this period was assessed. Results: A total of 721 patients with cervical fractures were included, of whom 417 underwent CTAs (57.8%). Sixty-eight BCVIs and seven strokes were diagnosed in this cohort. All algorithms detected an equivalent number of BCVIs (52 with the novel metric, 54 with the ACS and Denver Criteria, P = 0.84) and strokes (7/7, 100% with the novel metric, 6/7, 85.7% with the ACS and Denver Criteria, P = 1.0). However, 63% fewer scans would have been needed with the proposed screening algorithm compared with the ACS or Denver Criteria (261/721, 36.2% of all patients with our criteria vs . 413/721, 57.3% with the ACS standard and 417/721, 57.8%) with the Denver Criteria, P < 0.0002 for each). Conclusion: A two-step criterion based on mechanism of injury and patient factors is a potentially useful guide for identifying patients at risk of BCVI and stroke after cervical spine fractures. Further prospective analyses are required prior to widespread clinical adoption. Level of Evidence: 4. Abstract : A two-step screening criterion was developed to indicate computed tomography angiography (CTA) screening for blunt cerebrovascular injury (BCVI) after a cervical spine fracture. When assessed retrospectively, this criterion indicated 63% fewer patients for CTA versus the gold standard ACS and expanded Denver criteria, but detected an equivalent number of BCVI/traumatic strokes.